(untitled) (Journal of Applied Learning and Teaching, 2019)
Reading in a modern foreign language is not an easy task. In the most recent programme of study (DfE, 2013), students at Key Stage 3 are required to develop – amongst many other skills – reading. Desired skills include comprehension of original passages, from a range of different sources, with the view to not only understand the ideas communicated but also be able to translate them in accurate English. Furthermore, literary texts are to be used to “stimulate ideas” and develop “creative expression” (DfE, 2013, p. 1) with the aim to “expand understanding of the language and culture”. Within this context, the article aims to discuss the need that teachers face to develop reading in their classrooms and how it can be achieved. As with every other skill – listening, writing, speaking – it is important to nurture reading from a very early stage of learning. The case studies will demonstrate the possibility and accessibility of longer passages at an early stage of learning and will exemplify how to move the students away from rote learning and memorisation of vocabulary. Case studies will also show how reading can lead towards the development of other skills such as speaking, listening and writing.